The androgen receptor depends on ligand‐binding domain dimerization for transcriptional activation. (18th October 2021) - El Kharraz, Sarah; Dubois, Vanessa; van Royen, Martin E; Houtsmuller, Adriaan B; Pavlova, Ekatarina; Atanassova, Nina; Nguyen, Tien; Voet, Arnout; Eerlings, Roy; Handle, Florian; Prekovic, Stefan; Smeets, Elien; et al.
Abstract: Whereas dimerization of the DNA‐binding domain of the androgen receptor (AR) plays an evident role in recognizing bipartite response elements, the contribution of the dimerization of the ligand‐binding domain (LBD) to the correct functioning of the AR remains unclear. Here, we describe a mouse model with disrupted dimerization of the AR LBD (AR Lmon/Y ). The disruptive effect of the mutation is demonstrated by the feminized phenotype, absence of male accessory sex glands, and strongly affected spermatogenesis, despite high circulating levels of testosterone. Testosterone replacement studies in orchidectomized mice demonstrate that androgen‐regulated transcriptomes in AR Lmon/Y mice are completely lost. The mutated AR still translocates to the nucleus and binds chromatin, but does not bind to specific AR binding sites. In vitro studies reveal that the mutation in the LBD dimer interface also affects other AR functions such as DNA binding, ligand binding, and co‐regulator binding. In conclusion, LBD dimerization is crucial for the development of AR‐dependent tissues through its role in transcriptional regulation in vivo . Our findings identify AR LBD dimerization as a possible target for AR inhibition. Synopsis: This study reveals the contribution of ligand‐binding domain (LBD) dimerization to androgen receptor (AR) activity. Disrupting LBD dimerization affects multiple receptor functions, proposing this interface as new therapeutic target. Disrupting LBD dimerization in vitro slightly reduces ligand and DNA binding, interactions with a subset of coregulators as well as transactivation. In vivo, it leads to androgen insensitivity with absence of accessory sex glands, despite high circulating LH, testosterone and androstenedione levels. In vivo, the mutation leads to loss of binding to AR binding sites in chromatin, despite nuclear translocation and chromatin binding. In the testis, the AR regulates expression of HSD17B3, the enzyme which converts androstenedione into testosterone. Abstract : This study reveals the contribution of ligand‐binding domain (LBD) dimerization to androgen receptor (AR) activity. Disrupting LBD dimerization affects multiple receptor functions, proposing this interface as new therapeutic target.